Mary Wollstonecraft and the Right to Air. Issue 2 (July 2021) - Boyson, Rowan
Abstract : Air flows through all Mary Wollstonecraft's writings, from her first novel Mary, through her treatises and letters, and to her last novel Maria . She was attuned to the medical importance of a change of air, but also developed a more philosophical notion of a right to air. Her attention to everyday air and smell unavoidably reaffirmed her key intellectual questions of commonality, individuality, equality and freedom. For Wollstonecraft, air was both a metaphor for freedom and also a literal condition for its development. This article situates her numerous remarks on air alongside medical sources, racialized climatological theory, slavery cases, and the pneumatic chemistry of the 1790s. Such a reading of Wollstonecraft's aerial philosophy, and comparisons with Burke, Rousseau, Godwin and Kant, contributes to an ecological reading of her work and to a forgotten history of air rights, with relevance to current debates on air quality and inequality.